Anthropometric Measurement Training for Youth Cadres in Integrated Posted Cooperation (Posbindu) with Five Table System - Yunita Indah Prasetyaningrum (LPPM Universitas Yudharta Pasuruan, 2023)
Karangmojo Hamlet is one of the areas with the largest number of adolescents, so it has the potential to form a health behavior change agent. The existence of the Covid-19 pandemic has stopped monitoring the nutritional status of adolescents through health facilities, so it is necessary to carry out activities to improve public health status through the use of posbindu. However, on the other hand the youth cadres in Karangmojo have not been able to properly and correctly measure nutritional status. The purpose this community service activity is to increase the knowledge and skills of youth cadre regarding anthropometric measurement of nutritional status. The target of the community service is cadre Parikesit Damarwulan posbindu Karangmojo Hamlet. A series of community service activities be carried out in 2021 which began with focused discussions to identify problems faced by posbindu cadre. The design of activities with the design of one group pretest-posttest and mix method through three methods: education, simulation, and mentoring. Training provided on how to measure and categorize nutritional status based on anthropometry. After the training activities continued with assistance to cadre during posbindu activities. Assessment of changes in knowledge using a questionnaire and assessment of changes in cadre skills is carried out from the results of observations using a structured checklist. The training activities were able to increase the knowledge (p=0.024) and skills of youth cadre on measuring nutritional status at the Parikesit Damarwulan Posbindu.